2005
DOI: 10.1111/j.1365-2958.2005.04888.x
|View full text |Cite
|
Sign up to set email alerts
|

The liver stage of Plasmodium berghei inhibits host cell apoptosis

Abstract: SummaryPlasmodium berghei is the causative agent of rodent malaria and is widely used as a model system to study the liver stage of Plasmodium parasites. The entry of P. berghei sporozoites into hepatocytes has extensively been studied, but little is known about parasite-host interaction during later developmental stages of the intracellular parasite. Growth of the parasite far beyond the normal size of the host cell is an important stress factor for the infected cell. Cell stress is known to trigger programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 35 publications
5
108
0
1
Order By: Relevance
“…This kind of condition is likely to operate among the populations that live in malaria endemic areas, thereby explaining the absence of protective immune responses against the infection even after repeated exposures to the parasite. It has also been shown earlier that infected cells are protected from apoptosis by hepatocyte growth factor/MET signaling (44,45). Our results are also supported by the findings of Bongfen et al, who demonstrated that CSP, an immunodominant spz surface protein, is processed and presented by both traversed and infected primary hepatocytes and that they were both efficiently lysed by CSP-specific CTLs, apparently via perforin/granzyme mobilization (16).…”
Section: Discussionsupporting
confidence: 80%
“…This kind of condition is likely to operate among the populations that live in malaria endemic areas, thereby explaining the absence of protective immune responses against the infection even after repeated exposures to the parasite. It has also been shown earlier that infected cells are protected from apoptosis by hepatocyte growth factor/MET signaling (44,45). Our results are also supported by the findings of Bongfen et al, who demonstrated that CSP, an immunodominant spz surface protein, is processed and presented by both traversed and infected primary hepatocytes and that they were both efficiently lysed by CSP-specific CTLs, apparently via perforin/granzyme mobilization (16).…”
Section: Discussionsupporting
confidence: 80%
“…This is in conformity with studies which have shown that infected cells are protected from apoptosis (42,43). In addition, the finding that Fas-and perforin-deficient mice could still be protected from P. berghei (44) and P. yoelii (45) infection suggests that other mechanisms are implicated in the destruction of hepatic forms.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, even though apoptosis, induced in infected cells by cytotoxic immune effector cells, is a critical defense against intracellular pathogens, many viral, bacterial, and protozoan pathogens have developed mechanisms to invade and multiply within host cells without inducing apoptosis (6 -10). Various parasites undermine the apoptotic progression that includes Chlamydia, Escherichia coli, Mycobacterium tuberculosis, Toxoplasma gondii, Plasmodium berghei, and Leishmania species (11)(12)(13)(14)(15)(16)(17). Leishmania donovani was the first parasite reported to enhance host cell viability by inhibiting growth factor deprivation-induced apoptosis.…”
mentioning
confidence: 99%